Pengaruh Insider Ownership, Investment Opportunity Set (IOS), Pertumbuhan Perusahaan dan Risiko Bisnis terhadap Kebijakan Hutang - Megawati, Megawati -; Kurnia, Suci (Jurnal Kajian Manajemen Bisnis, 2015)
The aim of this research was to analyse the influence of insider ownership, investment opportunity set, firm growth, and business risk toward corporate debt policy on property and real estate in Indonesia stock exchange. The population for this research was all property and real estate company listed in Indonesian stock exchange for 2010-2013. The sample was determined by purposive sampling contained of 68 samples. The method of analysis used in this research was multiple regressions. The results shows that: 1) Insider Ownership gave negative influence and significant toward corporate debt policy on property and real estate in Indonesia stock exchange, 2) investment opportunity set gave positive influence and significant toward corporate debt policy on property and real estate in Indonesian stock exchange, 3) the firm growth gave positive influence but not significant toward corporate debt policy on property and real estate in Indonesian stock exchange, 4) the business risk gave negative influence and significant to ward corporate debt policy on property and real estate in Indonesian stock exchange.